Film in biography form: the use of pre-existing classical music in the composer biopic - Farrell-Griffiths, Naomi (2019)
Kathryn Kalinak describes film music as being ‘directly composed’ to accompany motion pictures, with its function found in enhancing the emotional and narrative structures of the onscreen events, such as dialogue, screenplay, and acting. (Kalinak, 2010). An exception to this arises when a film makes use of pre-existing music as its soundtrack. Pre-existing music is composed without knowledge of a film’s emotional or narrative properties and is therefore not specifically composed for the film. Nowhere is this phenomenon seen clearer than in the composer biopic, which, due to its subject matter, often demands the use of pre-existing music. The recontextualisation of pre-existing classical music into a filmic context means that it can now be cast in a new light, intertwined with a scene’s sentiment. However, does the adoption of a filmic context mean that the use of pre-existing music should be assessed by film music criteria, such as the amplification of mood and narrative? If so, does that consequence a loss of musical integrity? Furthermore, what are the repercussions of this changing context for our understanding and interpretation of the original music?